Strategy for Leukemia Treatment Targeting SHP-1,2 and SHIP - Hao, Fang; Wang, Chen; Sholy, Christine; Cao, Min; Kang, Xunlei (Frontiers in Cell and Developmental Biology, 2021)
Protein tyrosine phosphatases (PTPs) are modulators of cellular functions such as differentiation, metabolism, migration, and survival. PTPs antagonize tyrosine kinases by removing phosphate moieties from molecular signaling residues, thus inhibiting signal transduction. Two PTPs, SHP-1 and SHP-2 (SH2 domain-containing phosphatases 1 and 2, respectively) and another inhibitory phosphatase, SHIP (SH2 domain-containing inositol phosphatase), are essential for cell function, which is reflected in the defective phenotype of mutant mice. Interestingly, SHP-1, SHP-2, and SHIP mutations are identified in many cases of human leukemia. However, the impact of these phosphatases and their mutations regarding the onset and progression of leukemia is controversial. The ambiguity of the role of these phosphatases imposes challenges on the development of targeting therapies for leukemia. This fundamental problem, confronted by the expanding investigational field of leukemia, will be addressed in this review, which will include a discussion of the molecular mechanisms of SHP-1, SHP-2, and SHIP in normal hematopoiesis and their role in leukemia. Clinical development of leukemic therapies achieved by targeting these phosphatases will be addressed as well.